2018
DOI: 10.30998/scope.v2i01.2273
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Neurolinguistic Programming (NlP) Methods Towards Students’ Speaking Skill

Abstract: <p>The objective of this research is to investigate the effects of Neurolinguistic Programming (NLP) method towards students’ speaking skill at Madrasah Ibtidaiyah Sa’adatuddarain 2 Tangerang Selatan. This research was conducted at Madrasah Ibtidaiyah Sa’adatuddarain 2 Tangerang Selatan from April 15<sup>th </sup>2016-July 15<sup>th </sup>2016.  By using purposive sampling technique, 60 out of 300 students of grade V in school year 2015-2016 were chosen. The method used was a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…All studies that examine aspects of speaking skills also showed a significant increase in results. The NLP method has a positive and significant impact on students' English-speaking skills compared to conventional methods (Fidinillah, 2018). NLP helps EFL learners pronounce past regular verb endings (Caballero & Rosado, 2018).…”
Section: B Language Acquisition Through the Nlp Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies that examine aspects of speaking skills also showed a significant increase in results. The NLP method has a positive and significant impact on students' English-speaking skills compared to conventional methods (Fidinillah, 2018). NLP helps EFL learners pronounce past regular verb endings (Caballero & Rosado, 2018).…”
Section: B Language Acquisition Through the Nlp Approachmentioning
confidence: 99%
“…Four articles examined students' writing skills, including one report that examined creative writing skills (Rustan, 2017), one that discussed narrative text writing skills (Rumawan & Suharti, 2018), and two that examined writing skills in general (Pratama et al, 2019;Wikanengsih, 2013). English-speaking skills were assessed by three studies (Caballero & Rosado, 2018;Fidinillah, 2018;Vaezi & Shahroosvand, 2015). In addition, one article examined reading comprehension skills (Farahani, 2018) and one examined listening comprehension (Khalandi & Zoghi, 2017).…”
Section: Aspects Of Language Learningmentioning
confidence: 99%
See 1 more Smart Citation